Stabilizing the Homopolycation (I4)2+ with a Hexasulfate in (I4)[S6O19] and a Borosulfate in (I4)[B(S2O7)2]2. Issue 11 (20th July 2022) - van Gerven, David; Sutorius, Stefan; Bruns, Jörn; Wickleder, Mathias S.
Abstract: The reaction of elemental iodine and SO3 in a sealed glass ampoule yielded a turquoise‐colored solution. At temperatures below 7 °C, deep red crystals of (I4 )[S6 O19 ] grow. With the addition of B2 O3 and pyridine‐SO3 complex red crystals of (I4 )[B(S2 O7 )2 ]2 can be obtained after heating the mixture to 120 °C. The combination of an (I4 ) 2+ cation with oxoanions has previously not been observed. Both anions have a significant but different influence on the structural properties of the (I4 ) 2+ cation. Abstract : The (I4 ) 2+ cation has been stabilized by a hexasulfate and a borosulfate anion in the compounds (I4 )[S6 O19 ] and (I4 )[B(S2 O7 )2 ]2 . Both occur as red crystals and can only be achieved from reactions with SO3 . While the cation‐anion interactions have strong influence on the structure of hexasulfate anion, the severe coordination of multiple borosulfate anions causes significant changes in the cation geometry.